Effectiveness of the use of ventilator training program among nurses at Thungsong Hospital in Nakhon Si Thammarat Province - Boonmuang, Nutchanok (Thai Journal of Nursing, 2021)
This quasi-experimental research aimed to evaluate effectiveness of the use of ventilator training program among nurses at Thungsong Hospital in Nakhon Si Thammarat Province. The sample of 111 professional nurses working at Thungsong Hospital, was purposively selected. The research instruments included the use of ventilator training program, a demographic data questionnaire, the knowledge test on mechanical ventilator, and the skill assessment on the use of mechanical ventilator. Its content validity index was 0.98, and the reliability coefficients (KR-20) of the knowledge test and the skill assessment were 0.89 and 0.91 respectively. The data were analyzed using descriptive statistics and t-test. The results showed that before the training, less than half of nurses (49.5%) had knowledge on mechanical ventilator at the low level and 31.5 percent of them were at the moderate level. After the training, almost all of them (98.2 %) had the high level of knowledge. Before the training, 86.50 percent of them had skill on the use of mechanical ventilator at the low level, but after training their scores increased to the moderate level (56.80%) and high level (32.40%). Their knowledge and skill on the use of mechanical ventilator after the training were significantly higher than those before the training at p < .05.